Pengembangan Sistem Informasi Manajemen Layanan Perpustakaan SMK Merdeka Bandung - Soetedjo, Agung; Sidik, Rangga (Jurnal Teknologi dan Informasi (JATI), 2019)
The library becomes an important place for students, as well as educators in finding information about knowledge. The presence of technology must be able to be used by libraries to improve library of services and accessibility to information. The library at SMK Merdeka Bandung requires the application of information technology as a supporting tool for managing library service activities. Library activity services have not been able to run well marked with several obstacles that arise. The purpose of this study is to make the library at SMK Merdeka Bandung able to apply information technology in the form of computerized information systems in the services as provided to library members. The study was conducted using qualitative descriptive methods with the method of developing protoyping systems and structured approach models. Development of information system applications using the Java programming language. The results of this research can produce a desktop-based information system application that is capable of handling library services including; member registration services, loans, returns, stock, library catalog services, and damage and loss replacement services. With the application of this information system can make library activities at Merdeka Vocational School Bandung become more computerized so that the problems that arise can be resolved properly.